The negative off-response driven by M-cone and depolarizing bipolar cell in the rat electroretinogram - Tao Chen; Yuting Su; Weiming Yan; Junhui Xue; Zuoming Zhang (Scientific Reports)
Abstract To elucidate the contributions of M-cone to the negative off-response of rat Electroretinogram (ERG) using specific drugs and spontaneous mutation rat models. The ON/OFF responses of ERG were evoked by long duration flash (200 ms) pre or post the application of 2-amino-4-phosphonobutyric acid (APB), cis-piperidine-2,3-dicarboxylic acid (PDA) or BaCl2 to the Sprague-Dawley (SD) rats. Furthermore, the ON/OFF responses of other two types of mutation rats, the middle-wavelength opsin cone dysfunction (MCD) rats and congenital stationary night blindness (CSNB) rats, were recorded. Typical scotopic and photopic ON/OFF responses were recorded in SD rats. At light offset, the OFF response showed a rapid negative deflection, then the retinal potential slowly returned to baseline from the trough of the negative off-response. The negative off-response was completely eliminated by the intravitreal injection of 400 µM APB. The amplitude of the negative off-response was reduced by the application of 5 mM PDA. However, the off component was not blocked by the application of 50 µM BaCl2. In addition, distinct differences of OFF response were found among MCD, CSNB and SD rats. The scotopic ON/OFF ERG of the MCD and CSNB rats showed no obvious negative off component at light offset, while the negative off component of photopic ON/OFF ERG was found in the CSNB rats, though with lower amplitude. The negative off-response of rat ERGs is not the off component of M-wave: a negative potential change at stimulus onset or offset. M-cone and the depolarizing bipolar cell play a central role in the signal transmission of this negative off-response.